Acute toxicity of normofractionated intensity modulated radiotherapy with simultaneous integrated boost compared to three-dimensional conformal radiotherapy with sequential boost in the adjuvant treatment of breast cancer - Krug, David; Köder, Christine; Häfner, Matthias; Arians, Nathalie; Harrabi, Semi B.; Körber, Stefan A.; Forster, Tobias; Schlampp, Ingmar; Sohn, Christof; Heil, Jörg; Hof, Holger; Hörner-Rieber, Juliane; et al. (Radiation oncology, 2020)
Intensity-modulated radiotherapy (IMRT) improves dose homogeneity and late toxicity compared to simple tangential techniques in adjuvant whole-breast radiotherapy for patients with breast cancer. Simultaneous-integrated boost (SIB) radiotherapy shortens the overall treatment time and improves dose homogeneity. However, prospective randomized trials regarding IMRT with SIB for adjuvant radiotherapy in breast cancer are lacking.